Upper- vs. Lower-Body Exercise Performance in Female and Male Cross-Country Skiers - Hansen, Linda Marie; Sandbakk, Øyvind; Ettema, Gertjan; Baumgart, Julia Kathrin (Frontiers in Sports and Active Living, 2021)
Purpose: To investigate the interaction between exercise modality (i.e., upper- and lower-body exercise) and sex in physiological responses and power output (PO) across the entire intensity spectrum (i.e., from low to maximal intensity). Methods: Ten male and 10 female cross-country (XC) skiers performed a stepwise incremental test to exhaustion consisting of 5 min stages with increasing workload employing upper-body poling (UP) and running (RUN) on two separate days. Mixed measures ANOVA were performed to investigate the interactions between exercise modalities (i.e., UP and RUN) and sex in physiological responses and PO across the entire exercise intensity spectrum. Results: The difference between UP and RUN (ΔUP−RUN), was not different in the female compared with the male XC skiers for peak oxygen uptake (18 ± 6 vs. 18 ± 6 mL·kg−1·min−1, p = 0.843) and peak PO (84 ± 18 vs. 91 ± 22 W, p = 0.207). At most given blood lactate and rating of perceived exertion values, ΔUP−RUN was larger in the male compared with the female skiers for oxygen uptake and PO, but these differences disappeared when the responses were expressed as % of the modality-specific peak. Conclusion: Modality-differences (i.e., ΔUP−RUN) in peak physiological responses and PO did not differ between the female and male XC skiers. This indicates that increased focus on upper-body strength and endurance training in female skiers in recent years may have closed the gap between upper- and lower-body endurance capacity compared with male XC skiers. In addition, no sex-related considerations need to be made when using relative physiological responses for intensity regulation within a specific exercise modality.